New Method for Simultaneous Species-Specific Identification of Equine Strongyles (Nematoda, Strongylida) by Reverse Line Blot Hybridization - Traversa, Donato (American Society for Microbiology, 2007)
The ability of a reverse line blot (RLB) assay to identify 13 common species of equine small strongyles (cyathostomins) and to discriminate them from three Strongylus spp. (large strongyles) was demonstrated. The assay relied on the specific hybridization of PCR-amplified intergenic spacer DNA fragments of the nuclear ribosomal DNA to membrane-bound species-specific probes. All cyathostomins examined were unequivocally identified and simultaneously discriminated from each other and from three large strongyles (Strongylus edentatus, Strongylus equinus, and Strongylus vulgaris). This assay will enable the accurate and rapid identification of equine cyathostomins irrespective of their life cycle stage, opening important avenues for a better understanding of their biology and epidemiology and of the pathogenesis of cyathostomin-associated disease. In particular, this RLB method promises to be a powerful diagnostic tool to determine the roles of individual species in the pathogenesis of mixed infections and to elucidate some aspects of cyathostominosis. Also, it could represent a basic step toward the development of a rapid and simple molecular test for the early detection of drug-resistant genotypes of horse strongyle species.